Physiological and productivity responses of Tahiti acid lime grafted onto dwarfing rootstocks under different planting and mulching practices - Ana Júlia Borim de Souza; Mariângela Cristofani-Yaly; Patrícia Marluci da Conceição; Fernando Trevizan Devite; Marinês Bastianel; Paulo Vitor Sanches Romero; Pedro Henrique Barrio Padilha; Fernando Alves de Azevedo (Frontiers in Sustainable Food Systems)
Tahiti lime is one of the most exported fruits in Brazil, and the state of São Paulo accounts for more than half of the country’s fruit production, and drought in the region is a growing concern as rainfall distribution has become increasingly unpredictable. Therefore, identifying the best varieties and management strategies for citrus groves has become a subject of increasing research. This experiment was conducted at the “Sylvio Moreira” Citrus Center, Brazil; the experiment focused on different planting and mulching practices and scion-rootstock combinations. Two planting/management types were tested: (i) conventional tillage – CT (no mulch in the citrus row) and no-tillage – NT (mulch maintained in the citrus row), using Urochloa ruziziensis as an intercrop. Six grafts x rootstocks were tested: Tahiti acid IACC 5, IAC 10, and BRS IAC EECB Ponta Firme grafted onto two dwarf rootstocks: trifoliate orange IAC 718 Flying Dragon and citrandarin IAC 3152 Itajobi. Over three harvests (2022–2024), this study evaluated foliar nutrition, fruit quality, root development, water potential, gas exchange, water deficit biomarkers, and overall yield. No-tillage significantly improved vital performance indicators compared to conventional tillage. Plants managed with NT exhibited superior root development, greater water uptake, and greater leaf water potential. They also showed greater photosynthetic efficiency, leading to higher yields and improved fruit quality, particularly in juice yield and soluble solids/acidity ratio. The IAC 3152 Itajobi rootstock demonstrated remarkable resilience to drought stress, outperforming Flying Dragon in root development and physiological metrics. NT promoted healthier root systems and more robust plant growth. In contrast, conventional tillage led to poorer root growth, lower nutrient uptake, and increased disease susceptibility due to soil exposure and reduced water infiltration. Despite these challenges, 3,152 rootstock maintained active physiological responses such as gas exchange and/or water potential, especially with the Firm Tip graft. In conclusion, the integration of dwarf rootstocks with NT practices offers a viable strategy to increase the sustainability and productivity. This study highlights the importance of selecting appropriate scion-rootstock combinations and adopting sustainable management practices to improve resilience to environmental stress and optimize fruit yield and quality.